Optimization Objective Function Corona Discharge Acoustic Using Fuzzy c-Means (FcM ) - Fikri, Miftahul; Christiono, Christiono; Mulyana K, Iwa Garniwa; Ratnasari, Titi; Atmadja, Kurniawan; Thahara, Andi Amar; Romadhoni, Muhammad Luthfiansyah (Faculty of Engineering, Universitas Tanjungpura, 2023)
In many electrical networks in Indonesia, insulation failure due to high voltage phenomena like Corona Discharge (CD) still happens. This is a result of our inability to perform early Corona Discharge (CD) identification. This study